Evaluation of the efficacy of Abelmoschus manihot (L.) on diabetic nephropathy by analyzing biomarkers in the glomeruli and proximal and distal convoluted tubules of the kidneys - Yu, Hongmei; Wang, Mei; Yu, Jingshi; Tang, Haitao; Xu, Qing; Cheng, Ning; Luo, Xiaoxiao; Wang, Yurong; Ge, Haitao; Qiang, Lei; Tang, Wei; Gu, Harvest F. (Frontiers in Pharmacology, 2023)
As a traditional Chinese medicine, Abelmoschus manihot (L.) at the form of Huangkui capsule (HK) has been used for medication of kidney diseases, including diabetic nephropathy (DN), in China. The most significance of HK treatment in kidney diseases is the reduction of albuminuria and proteinuria. To evaluate the efficacy of HK in the regression of DN, in the current study, we have analyzed the biomarkers in glomerulus, proximal and distinct convoluted tubules in kidneys of db/db mice, the animal model for type 2 diabetes (T2D) and DN. Huangkui capsules (0.84 g/kg/d) or vehicle were administered daily via oral gavage for 4 weeks in db/db mice. Urinary albumin-tocreatinine ratio (UACR) and blood glucose levels were measured during whole experimental period. Five biomarkers in glomerulus, proximal and distinct convoluted tubules in kidneys, including col4a3, slc5a2, slc34a1, slc12a3 and slc4a1, were selected and their activities at mRNA and protein levels before and after HK treatment were analyzed with real time RT-PCR and immunohistochemistry. After HK treatment for 4 weeks, UACR in db/db mice was found to be significantly decreased. The activities of col4a3, slc5a2, slc34a1, slc12a3 and slc4a1 in kidneys were upregulated in db/db mice before but downregulated after HK treatment. Further analyses of the fields of whole kidney sections demonstrated that the number of nephron in kidneys of db/db mice with HK treatment was higher than what without HK treatment. Thereby, the current study provides experimental evidence confirming the medical efficacy of A. Manihot in reduction of albuminuria and proteinuria and suggesting that of A. Manihot may have the pharmacological efficacy in regression of the development of T2D-DN.